Patients’ Perspective About the Cost of Diabetes Management: An Analysis of Online Health Communities - Catherine C. Gao, MD; Nataly R. Espinoza Suarez, MD; Freddy J.K. Toloza, MD; Ariana S. Malaga Zuniga; Sarah R. McCarthy, PhD, MPH, LP; Kasey R. Boehmer, MPH, PhD; Lixia Yao, PhD; Sunyang Fu, PhD; Juan P. Brito, MD, MSc (Mayo Clinic Proceedings: Innovations, Quality & Outcomes, 2021)
Objective: To understand the perspectives of persons’ living with diabetes about the increasing cost of diabetes management through an analysis of online health communities (OHCs) and the impact of persons’ participation in OHCs on their capacity and treatment burden. Patients and Methods: A qualitative study of 556 blog posts submitted between January 1, 2007 and December 31, 2017 to 4 diabetes social networking sites was conducted between March 2018 and July 2019. All posts were coded inductively using thematic analysis procedures. Eton’s Burden of Treatment Framework and Boehmer’s Theory of Patient Capacity directed triangulation of themes with existing theory. Results: Three themes were identified: (1) cost barriers to care: participants describe individual and systemic cost barriers that inhibit prescribed therapy goals; (2) impact of financial cost on health: participants describe the financial effects of care on their physical and emotional health; and (3) saving strategies to overcome cost impact: participants discuss practical strategies that help them achieve therapy goals. Finally, we also identify that the use of OHCs serves to increase persons’ capacity with the potential to decrease treatment burden, ultimately improving mental and physical health. Conclusion: High cost for diabetes care generated barriers that negatively affected physical health and emotional states. Participant-shared experiences in OHCs increased participants’ capacity to manage the burden. Potential solutions include cost-based shared decision-making tools and advocacy for policy change.